Impaired Response Selection During Stepping Predicts Falls in Older People-A Cohort Study - Schöne, Daniel; Delbaere, Kim; Lord, Stephen R. (Journal of the American Medical Directors Association, 2017)
BACKGROUND: Response inhibition, an important executive function, has been identified as a risk factor for falls in older people. This study investigated whether step tests that include different levels of response inhibition differ in their ability to predict falls and whether such associations are mediated by measures of attention, speed, and/or balance. METHODS: A cohort study with a 12-month follow-up was conducted in community-dwelling older people without major cognitive and mobility impairments. Participants underwent 3 step tests: (1) choice stepping reaction time (CSRT) requiring rapid decision making and step initiation; (2) inhibitory choice stepping reaction time (iCSRT) requiring additional response inhibition and response-selection (go/no-go); and (3) a Stroop Stepping Test (SST) under congruent and incongruent conditions requiring conflict resolution. Participants also completed tests of processing speed, balance, and attention as potential mediators. RESULTS: Ninety-three of the 212 participants (44%) fell in the follow-up period. Of the step tests, only components of the iCSRT task predicted falls in this time with the relative risk per standard deviation for the reaction time (iCSRT-RT) = 1.23 (95%CI = 1.10-1.37). Multiple mediation analysis indicated that the iCSRT-RT was independently associated with falls and not mediated through slow processing speed, poor balance, or inattention. CONCLUSIONS: Combined stepping and response inhibition as measured in a go/no-go test stepping paradigm predicted falls in older people. This suggests that integrity of the response-selection component of a voluntary stepping response is crucial for minimizing fall risk.
EVALuna2:35570